A new parameter of geomagnetic storms for the severity of space weather - Balan, N.; Batista, I.S.; Tulasiram, S.; Rajesh, P.K. (My University, 2016)
Using the continuous Dst data available since 1957 and H component data for the Carrington space weather event of 1859, the paper shows that the mean value of Dst during the main phase of geomagnetic storms, called mean DstMP, is a unique parameter that can indicate the severity of space weather. All storms having high mean DstMP (≤−250 nT), which corresponds to high amount of energy input in the magnetosphere–ionosphere system in short duration, are found associated with severe space weather events that caused all known electric power outages and telegraph system failures.
Keywords: Space weather; Geomagnetic storms